Environmental DNA reveals spatial and vertical structuring of marine biodiversity in a Mediterranean biogeographic crossroads - Massimo Genovese; Carlo Pretti; Leandro Di Gloria; Anna Maria De Biasi; Lorenzo Casbarra; Bianca Gabbrielli; Joanna Giannessi; Matteo Oliva; Matteo Ramazzotti; Mariella Baratti (Marine Environmental Research, 2026)

Fluoroquinolone antibiotics impair sperm quality in the Mediterranean mussel Mytilus galloprovincialis - Joanna Giannessi; Lucia De Marchi; Alessia Cuccaro; Gianfranca Monni; Carlo Pretti (Aquatic Toxicology, 2026)

Traces in the water: eDNA reveals the return of the Eurasian otter Lutra lutra to central Italy - Mariella Baratti; Massimo Genovese; Leonardo Ancillotto; Alessandro Lagrotteria; Andrea Viviano; Carlo Pretti; Massimo Gori; Emiliano Mori (Conservation Genetics, 2026)

From metabolites to tissues: A comprehensive analysis of salinity-driven modulation of tetracycline effects in Mytilus galloprovincialis - Marta Cunha; Alessio Lenzi; Constança Figueiredo; Lucia De Marchi; Carla Leite; Tania Russo; Gianfranca Monni; Valentina Meucci; Amadeu M.V.M. Soares; Gianluca Polese; Eduarda Pereira; Carlo Pretti; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Hidden costs of beauty: An in vitro study on the ecotoxicological impacts of ultraviolet filters and parabens on the bioindicator species Mytilus galloprovincialis - Diana Bordalo; Amadeu M.V.M. Soares; Inna Sokolova; Carlo Pretti; Rosa Freitas (Marine Pollution Bulletin, 2025)

Biochemical dynamics of the invasive clams Ruditapes philippinarum and Corbicula fluminea in response to caffeine concentrations under present and future climate scenarios - Marta Cunha; Sofia Raimundo; Lucia De Marchi; Carla Leite; Carlo Pretti; Valentina Meucci; Amadeu M.V.M. Soares; Sara C. Antunes; Rosa Freitas (Estuarine, Coastal and Shelf Science, 2025)

Metagenomic surveys show a widespread diffusion of antibiotic resistance genes in a transect from urbanized to marine protected area - Tania Alonso-Vásquez; Camilla Fagorzi; Alessio Mengoni; Matteo Oliva; Duccio Cavalieri; Carlo Pretti; Lisa Cangioli; Giovanni Bacci; Alberto Ugolini (Marine Pollution Bulletin, 2025)

Drought immediately increases soluble sugar and decreases starch in seedlings of the shade-tolerant compared to the sun-tolerant ecotype of Paubrasilia echinata - Geraldo Rogério Faustini Cuzzuol; Carlos Luis Sánchez Fonseca; Moemy Gomes de Moraes; Bernardo Pretti Becacici Macieira (Flora, 2025)

Short alkyl-chained Imidazolium-based Ionic Liquids: Promising green solution or potential environmental threat? - Matilde Vieira Sanches; Matteo Oliva; Giorgia Fumagalli; Andrea Mezzetta; Lorenzo Guazzelli; Rosa Freitas; Carlo Pretti (Chemosphere, 2025)

2-Ethylhexyl-4-methoxycinnamate on marine and coastal environments: A comprehensive review of its environmental significance and biological impact - Diana Bordalo; Amadeu M.V.M. Soares; Inna Sokolova; Carlo Pretti; Rosa Freitas (Marine Pollution Bulletin, 2025)

Salinity modulation of neodymium and dysprosium toxicity in mussels: A comprehensive analysis of adult and sperm responses - Carla Leite; Tania Russo; Gianluca Polese; Amadeu M.V.M. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Science of The Total Environment, 2025)

Impacts of UV-filter pollution and low pH: Sperm and adult biomarkers in the mussel Mytilus galloprovincialis in a multi-stressor context. - Alessia Cuccaro; Anthony Moreira; Lucia De Marchi; Valentina Meucci; Amadeu M.V.M. Soares; Carlo Pretti; Rosa Freitas (Journal of Hazardous Materials, 2025)

Stress-Related Molecular Biomarkers to Monitor the Effects of Global Changes on Calcifying Reef-Forming Organisms: A Review in the Mediterranean - Verdiana Vellani; Matteo Oliva; Carlo Pretti; Monia Renzi (Journal of Marine Science and Engineering, 2024)
Molecular biomarkers are valuable tools universally used for early warning monitoring due to their ability to detect stress at subcellular scales, even before visible or lethal changes occur in organisms. Their use is considered a priority, especially for those organisms that will be most affected by the global changes underway, such as sessile benthic organisms in shallow waters. Among them, reef-forming species play a vital role in maintaining biodiversity in temperate aquatic ecosystems. Little information is available on these organisms in the Mediterranean on the use of health status indicators at the level of biochemical responses. This review aims to highlight the need for a more in-depth analysis of the conditions of bioconstructors in a climate change scenario by using stress biomarkers. To achieve this goal, about 140 articles were selected based on a keyword search for a graphical visualization of the state of the art of the literature. Based on this overview, a literature review of selected works in the Mediterranean area was conducted to select both model organisms and molecular biomarkers for future analyses in this field. From the literature review, a gap analysis was produced, focusing on the main stressors related to global change and their effects on bioconstructors. Furthermore, an attempt was made to quantify and clarify the use of the various molecular biomarkers in different contexts. These findings should be considered in an updated protocol for monitoring programs and efforts at the European level, as outlined by the Marine Strategy Framework Directive (MSFD 2008/56/EC).

Interplay of UV-filter pollution and temperature rise scenarios on Mytilus galloprovincialis health: Unveiling sperm quality and adult physiology, biochemistry, and histology insights - Alessia Cuccaro; Lucia De Marchi; Andrea Pirone; Gianfranca Monni; Valentina Meucci; Giulia Lazzarini; Giorgia Fumagalli; Matteo Oliva; Vincenzo Miragliotta; Rosa Freitas; Carlo Pretti (Environmental Pollution, 2024)

Rare earth elements and warming: Implications for adult mussel health and sperm quality - Carla Leite; Tania Russo; Alessia Cuccaro; João Pinto; Gianluca Polese; Amadeu M.V.M. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Marine Environmental Research, 2024)

PON1 enzyme activity assays for serum and heparinized plasma in horses and stability evaluation of the enzyme activity over different freeze-thaw cycles and mimic transportation - Matilde Vernaccini; Valentina Meucci; Francesca Bindi; Micaela Sgorbini; Carlo Pretti; Gianfranca Monni; Lucia de Marchi (Research in Veterinary Science, 2024)

Interrupting marine fouling with active buffered coatings - Riddhiman Medhi; Alexandra D. Handlin; Amanda K. Leonardi; Giancarlo Galli; Elisa Guazzelli; John A. Finlay; Anthony S. Clare; Matteo Oliva; Carlo Pretti; Elisa Martinelli; Christopher K. Ober (Biofouling, 2024)

Praseodymium and warming interactions in mussels: Comparison between observed and predicted results - Carla Leite; Tania Russo; Alessia Cuccaro; João Pinto; Gianluca Polese; Amadeu M.V.M. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Science of The Total Environment, 2024)

The role of warming in modulating neodymium effects on adults and sperm of Mytilus galloprovincialis - Carla Leite; Tania Russo; Alessia Cuccaro; João Pinto; Gianluca Polese; Amadeu MVM. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Journal of Environmental Management, 2024)

Assessing combined effects of long-term exposure to copper and marine heatwaves on the reef-forming serpulid Ficopomatus enigmaticus through a biomarker approach - Verdiana Vellani; Alessia Cuccaro; Matteo Oliva; Carlo Pretti; Monia Renzi (Marine Pollution Bulletin, 2024)

On the biology of blackbellied angler, Lophius budegassa Spinola, 1807, in the north-western Mediterranean - ANDREA MASSARO; CLAUDIA MUSUMECI; FRANCECO De CARLO; ALESSANDRO LIGAS; LOREDANA RUSSO; PIERLUIGI CARBONARA; CARLO PRETTI; PAOLO SARTOR (Mediterranean Marine Science, 2024)
In the Mediterranean Sea, the blackbellied angler, Lophius budegassa Spinola, 1807, represents a relevant fraction of the commercial by-catch of bottom trawling and small-scale fisheries that use passive gears (e.g., set nets, bottom longlines, etc.). Despite its importance, there are no comprehensive studies on the population dynamics of this species, and there is still scarce and scattered knowledge of its biology and ecology. Biomass, morphometric, and biological data of the blackbellied angler were collected from 1994 to 2021 by means of the Mediterranean International Bottom Trawl Survey (MEDITS) programme in the Ligurian and northern Tyrrhenian Seas, and in the EU Data Collection Framework during the period of 2006-2021. Furthermore, ageing was performed on specimens collected from 2013 to 2021 during the MEDITS programme. There were high values for the density indices and the spatial distribution of biomass in the central sector of the investigated area (the Tuscan Archipelago), mostly on the continental shelf. The length-weight relationship showed negative allometric growth when considering the sexes together, and no difference between the sexes. The size at first maturity (L50) was estimated at 39.4 cm total length (TL) in females and at 29.2 cm TL in males. The obtained Von Bertalanffy growth parameters were: in females, L∞ = 74.50 cm, k = 0.10 years-1, and t0 = -0.40 years; in males, L∞ = 61.30 cm, k = 0.14 years-1, and t0 = -0.38 years. There were differences in growth between males and females for L∞ (χ2 = 10.04; p

From the cellular to tissue alterations induced by two rare earth elements in the mussel species Mytilus galloprovincialis: Comparison between exposure and recovery periods - Carla Leite; Tania Russo; João Pinto; Gianluca Polese; Amadeu M.V.M. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Science of The Total Environment, 2024)

Pattern of prescriptions and prudent use of antimicrobial in horse practice at a Veterinary Teaching Hospital - Samanta Bacci; Valentina Meucci; Micaela Sgorbini; Lucia De Marchi; Andrea Pirone; Carlo Pretti; Rosalba Tognetti; Luigi Intorre (Research in Veterinary Science, 2024)

Exploring toxicological interactions in a changing sea: The case of the alkaloids caffeine and caulerpin - Tania Russo; Francesca Coppola; Debora Paris; Lucia De Marchi; Valentina Meucci; Andrea Motta; Marianna Carbone; Anna Di Cosmo; Amadeu M.V.M. Soares; Carlo Pretti; Ernesto Mollo; Rosa Freitas; et al. (Science of The Total Environment, 2024)

Ocean acidification impairs seagrass performance under thermal stress in shallow and deep water - Chiara Ravaglioli; Lucia De Marchi; Serena Anselmi; Emanuela Dattolo; Debora Fontanini; Carlo Pretti; Gabriele Procaccini; Gil Rilov; Monia Renzi; Jacob Silverman; Fabio Bulleri (Environmental Research, 2024)

Can temperature rise change the impacts induced by e-waste on adults and sperm of Mytilus galloprovincialis? - Carla Leite; Tania Russo; Alessia Cuccaro; João Pinto; Gianluca Polese; Amadeu M.V.M. Soares; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Science of The Total Environment, 2023)

Multi-biomarker approach for the (eco)toxicity of UV-filter environmental pollution on the Mediterranean mussel Mytilus galloprovincialis in a multiple stressor context. The case of 4-MBC under salinity shifts. - Alessia Cuccaro; Rosa Freitas; Lucia De Marchi; Gianfranca Monni; Valentina Meucci; Matteo Oliva; Giorgia Fumagalli; Carlo Pretti (Environmental Pollution, 2023)

Comparative subcellular responses to pharmaceutical exposures in the mussel Mytilus galloprovincialis: An in vitro study - Patrícia Cruz; Alessia Cuccaro; Carlo Pretti; Yide He; Amadeu M.V.M. Soares; Rosa Freitas (Environmental Toxicology and Pharmacology, 2023)

Subcellular tissue-specific responses of Mytilus galloprovincialis to fluoroquinolone antibiotics - Joanna Giannessi; Lucia De Marchi; Valentina Meucci; Luigi Intorre; Gianfranca Monni; Mariella Baratti; Carlo Pretti (Environmental Toxicology and Pharmacology, 2023)

In vitro screening of imidazolium and pyrrolidinium based ionic liquids toxicity on subcellular fractions of the Mediterranean mussel Mytilus galloprovincialis - Matilde Vieira Sanches; Matteo Oliva; Andrea Mezzetta; Lorenzo Guazzelli; Lucia De Marchi; Rosa Freitas; Carlo Pretti (Environmental Toxicology and Pharmacology, 2023)

Sub-lethal effects induced in Mytilus galloprovincialis after short-term exposure to sodium lauryl sulfate: Comparison of the biological responses given by mussels under two temperature scenarios - Sofia Paciello; Tania Russo; Lucia De Marchi; Amadeu M.V.M. Soares; Valentina Meucci; Carlo Pretti; Yide He; Camila Della Torre; Rosa Freitas (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Introducing energy into marine environments: A lab-scale static magnetic field submarine cable simulation and its effects on sperm and larval development on a reef forming serpulid - Matteo Oliva; Lucia De Marchi; Alessia Cuccaro; Giorgia Fumagalli; Rosa Freitas; Nunzia Fontana; Marco Raugi; Sami Barmada; Carlo Pretti (Environmental Pollution, 2023)

Combined effects of temperature rise and sodium lauryl sulfate in the Mediterranean mussel - Rosa Freitas; Federica Arrigo; Francesca Coppola; Valentina Meucci; Federica Battaglia; Amadeu M.V.M. Soares; Carlo Pretti; Caterina Faggio (Environmental Toxicology and Pharmacology, 2023)

Will warmer summers increase the impact of UV filters on marine bivalves? - Diana Bordalo; Alessia Cuccaro; Valentina Meucci; Lucia De Marchi; Amadeu M.V.M. Soares; Carlo Pretti; Rosa Freitas (Science of The Total Environment, 2023)

Toxic effects of a mixture of pharmaceuticals in Mytilus galloprovincialis: The case of 17α-ethinylestradiol and salicylic acid - Marta Cunha; Mónica G. Silva; Lucia De Marchi; Rui G. Morgado; Valdemar I. Esteves; Valentina Meucci; Federica Battaglia; Amadeu MVM. Soares; Carlo Pretti; Rosa Freitas (Environmental Pollution, 2023)

A forecast effects of climate change and anthropogenic compounds in Gambusia holbrooki: ecotoxicological effects of salinity and metformin - Maria Sousa; Sara Rodrigues; Carlo Pretti; Valentina Meucci; Federica Battaglia; Rosa Freitas; Sara C Antunes (Aquatic Toxicology, 2023)

Toxicity of ionic liquids in marine and freshwater microorganisms and invertebrates: state of the art - Matilde Vieira Sanches; Rosa Freitas; Matteo Oliva; Alessia Cuccaro; Gianfranca Monni; Andrea Mezzetta; Lorenzo Guazzelli; Carlo Pretti (Environmental Science and Pollution Research, 2023)

A multidisciplinary integrated approach using Pachygrapsus marmoratus to assess the impact of port activities on mediterranean marine protected areas - Ilaria Caliani; Stefano Cannicci; Carlo Pretti; Mariella Baratti; Ginevra Contini; Matteo Vitale; Silvia Casini; Maria Cristina Fossi; Alessio Iannucci; Sara Fratini (Chemosphere, 2023)

Can temperature influence the impacts induced in Mytilus galloprovincialis by neodymium? Comparison between exposure and recovery periods - Carla Leite; Francesca Coppola; Vanessa Queirós; Tania Russo; Gianluca Polese; Carlo Pretti; Eduarda Pereira; Rosa Freitas (Environmental Toxicology and Pharmacology, 2023)

Gene expression and biochemical patterns in the digestive gland of the mussel Mytilus galloprovincialis (Lamarck, 1819) exposed to 17α-ethinylestradiol - Carlo Pretti; Paolo Aretini; Francesca Lessi; Rosa Freitas; Carlos Barata; Lucia De Marchi; Alessia Cuccaro; Matteo Oliva; Valentina Meucci; Mariella Baratti (Aquatic Toxicology, 2023)

Testing experimental devices in the extension piece to increase the selectivity of bottom trawl in the Nw Mediterranean - Mario Sbrana; Francesco De Carlo; Alessandro Ligas; Andrea Massaro; Claudia Musumeci; Ilaria Rossetti; Marina Sartini; Claudio Vasapollo; Claudio Viva; Paolo Sartor; Carlo Pretti (Frontiers in Marine Science, 2022)
In the Mediterranean, experiments and technical measures aimed at improving the selectivity of bottom trawl nets mostly concern modifications to the codend. Grids have been tested in various areas, but have not been adopted for management purposes so far. The present study aims to evaluate whether the adoption of diamond meshes turned by 90° (T90 configuration) and a selection grid with 2 cm bar spacing, both placed in the extension piece of a commercial bottom trawl net, can contribute in reducing the capture of specimens under the Minimum Conservation Reference Size (MCRS) for the main commercial species. The results indicated that the T90 configuration has no effect compared to the commercial net commonly used by fishers. The grid showed a reduction of the catches of European hake individuals between 11 and 19 cm Total Length (TL). However, the use of this device reduced the catch of many species, such as red mullet, deep-water rose shrimp and broad tail short fin squid. This reduction was observed also for specimens above MCRS. In conclusion, the T90 applied to the extension piece does not provide any improvement in selectivity, contrary to what has been observed when the T90 is placed at the codend. In contrast, the grid could be a possible way to increase selectivity. However, the use of grid should be further investigated to identify settings that can avoid the loss of a substantial fraction of commercial catch.

Posidonia oceanica (L.) (Delile, 1813) extracts as a potential booster biocide in fouling-release coatings - Matteo Oliva; Elisa Martinelli; Elisa Guazzelli; Alessia Cuccaro; Lucia De Marchi; Giorgia Fumagalli; Gianfranca Monni; Marzia Vasarri; Donatella Degl’Innocenti; Carlo Pretti (Environmental Science and Pollution Research, 2022)

Are natural deep eutectic solvents always a sustainable option? A bioassay-based study - Matilde Vieira Sanches; Rosa Freitas; Matteo Oliva; Angelica Mero; Lucia De Marchi; Alessia Cuccaro; Giorgia Fumagalli; Andrea Mezzetta; Greta Colombo Dugoni; Monica Ferro; Andrea Mele; Lorenzo Guazzelli; et al. (Environmental Science and Pollution Research, 2022)
The traditional use of organic solvents in various branches of industry is being rethought as these compounds very often display high volatility, toxicity and lipophilicity (related to the ability to interact with biological membranes). More recently, developments in the field of Green Chemistry are focusing on the design of more sustainable and cost-effective solvent alternatives like Ionic Liquids (ILs), bio-based solvents and natural deep eutectic solvents (NADESs). The present study aimed at performing an ecotoxicological screening of 15 NADESs using an extensive set of marine and freshwater bioassays, based on different endpoints as the following: immobilization of the crustacean Daphnia magna , growth inhibition of Raphidocelis subcapitata and of Phaeodactylum tricornutum , larval development alterations on the serpulid Ficopomatus enigmaticus and bioluminescence inhibition of Aliivibrio fischeri . What emerged was a general absence of toxicity of all samples. However, both algal assays showed a certain degree of biostimulation, up to over 100% growth increase in respect to controls with 8 out of 15 compounds tested with Raphidocelis subcapitata . Despite NADESs-induced negligible toxicity effects to invertebrates, encouraging their labelling as “sustainable” solvents, the liability of their intentional or accidental release into aquatic systems may represent a serious risk in terms of ecosystem functioning impairments.

UV-filters in marine environments: a review of research trends, meta-analysis, and ecotoxicological impacts of 4-methylbenzylidene-camphor and benzophenone-3 on marine invertebrate communities - Alessia Cuccaro; Rosa Freitas; Lucia De Marchi; Matteo Oliva; Carlo Pretti (Environmental Science and Pollution Research, 2022)

A multi-bioassay integrated approach to assess antifouling potential of extracts from the Mediterranean sponge Ircinia oros - Lucia De Marchi; Carlo Pretti; Alessia Cuccaro; Matteo Oliva; Federica Tardelli; Gianfranca Monni; Michele Magri; Fabio Bulleri (Environmental Science and Pollution Research, 2022)
The phylum Porifera and their symbionts produce a wide variety of bioactive compounds, playing a central role in their ecology and evolution. In this study, four different extracts (obtained by non-polar and semi-polar extraction methodologies) of the Mediterranean sponge Ircinia oros were tested through a multi-bioassay integrated approach to assess their antifouling potential. Tests were performed using three common species, associated with three different endpoints: the marine bacterium Aliivibrio fischeri (inhibition of bioluminescence), the marine diatom Phaeodactylum tricornutum (inhibition of growth), and different development stages of the brackish water serpulid Ficopomatus enigmaticus (gametes: sperm motion, vitality inhibition and cellular damage; larvae: development; adults: AChE (acetylcholinesterase)-inhibitory activity). The effects of extracts were species specific and did not vary among different extraction methodologies. In particular, no significant reduction of bioluminescence of A. fischeri was observed for all tested samples. By contrast, extracts inhibited P. tricornutum growth and had toxic effects on different F. enigmaticus ’ developmental stages. Our results suggest that the proposed test battery can be considered a suitable tool as bioactivity screening of marine natural products.

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

Ecotoxicological Investigation in Three Model Species Exposed to Elutriates of Marine Sediments Inoculated With Bioplastics - Tommaso Campani; Silvia Casini; Ilaria Caliani; Carlo Pretti; Maria Cristina Fossi (Frontiers in Marine Science, 2020)

Expression of MicroRNAs miR-145, miR-181c, miR-199a and miR-1183 in the Blood and Hippocampus of Patients with Mesial Temporal Lobe Epilepsy - Luana Grupioni Lourenço Antônio; Priscila Freitas-Lima; Gabriela Pereira-da-Silva; João Alberto Assirati; Caio Marconato Matias; Mucio Luiz Assis Cirino; Luis Fernando Tirapelli; Tonicarlo Rodrigues Velasco; Americo Ceiki Sakamoto; Carlos Gilberto Carlotti; Daniela Pretti da Cunha Tirapelli (Journal of Molecular Neuroscience, 2019)

Impacts of ocean acidification on carboxylated carbon nanotube effects induced in the clam species Ruditapes philippinarum - Lucia De Marchi; Carlo Pretti; Federica Chiellini; Andrea Morelli; Victor Neto; Amadeu M.V.M. Soares; Etelvina Figueira; Rosa Freitas (Environmental Science and Pollution Research, 2019)

Determination of ochratoxin A in tissues of wild boar (Sus scrofa L.) by enzymatic digestion (ED) coupled to high-performance liquid chromatography with a fluorescence detector (HPLC-FLD) - Giacomo Luci; Luigi Intorre; Guido Ferruzzi; Danilo Mani; Lorella Giuliotti; Carlo Pretti; Rosalba Tognetti; Simone Bertini; Valentina Meucci (Mycotoxin Research, 2018)